EXPLORING THE ROLE OF KEY AUDIT MATTERS DISCLOSURE IN MITIGATING INVESTMENT RISK - Kuswanto, Randy; Angelita (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2025)
This study examines the impact of Key Audit Matters (KAM) disclosures on investment risk in the context of Indonesia’s evolving audit transparency landscape. The research is motivated by the implementation of SA701, which requires KAM disclosures in audit reports. The purpose of this study is to investigate how different aspects of KAM disclosures influence investor perceptions of risk. Using a quantitative approach, we analyze data from more than 700,000 stock data points and 1,358 firm-year observations of companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2023. Regression analysis reveals that detailed KAM disclosures (KAM2) significantly reduce investment risk, while the number of KAM disclosed (KAM1) and monetary information (KAM3) show no significant effect. These findings highlight the importance of contextual and thorough audit disclosures in reducing information asymmetry. The study contributes to the literature by emphasizing the role of audit transparency in emerging markets and provides practical recommendations for regulators to enhance KAM reporting standards.